Modeling Photovoltaic String in PLECS Under Partial Shading - (:unkn) unknown (IEEE, 2019)
The industry of solar energy and its application areas have developed and received much attention over the last two decades. Therefore, the types of photovoltaic (PV) system simulations are investigated and mostly discussed models close to the physical behaviour of a PV panel or system. Under the real conditions such as cloud coverage, the shadows of nearby objects, dusty air, and dirty surface area, etc. result in partial shading issue, which is the core problem of predicting how the system behaves electrically. This paper describes the electrical behaviour model of an established PV string consisting of an experimental curve of CHN250-60P panel shown in the datasheet. The simulation model is performed through the instrumentality of Piecewise Linear Electrical Simulation (PLECS) Block-set in MATLAB/Simulink platform. With the proposed model, the I-V and P-V curves of the system can be represented according to the values of a 3D Lookup Table (LUT). Consequently, the simulation results are dealt with partial shading issue to verify a correct model in different solar irradiance and temperature.
Keywords: Photovoltaic systems; PLECS (R); modeling; MATLAB; partial shading